PERILAKU WANITA USIA SUBUR TERHADAP MINAT DALAM PENCEGAHAN KANKER SERVIKS DI PUSKESMAS KAMPUNG BARU - Ninsah Mandala Putri; Gusti Artha Nainggolan; Astaria Br. Ginting; Keiza S.A Rajagukguk (Nindikayla Institute, 2026)
Cervical cancer is one of the leading causes of morbidity and mortality among women in Indonesia. Although it can be prevented through Human Papillomavirus (HPV) vaccination and early detection using IVA screening or Pap smears, screening coverage remains low due to a lack of knowledge, attitudes, and awareness among women of childbearing age. This study aims to analyze the behavior of women of reproductive age regarding their interest in cervical cancer prevention at the Kampung Baru Community Health Center. The study employed a quantitative analytical design with a cross-sectional approach. The sample consisted of 98 women of reproductive age selected using purposive sampling. Data were collected using a questionnaire that measured respondents’ behavior and interest in cervical cancer prevention. The results showed that the majority of respondents were aged 26–35 years (41.8%) and had a high school education (45.9%). The behavior of the respondents was classified as “good” for 56 individuals (57.1%), while 62 respondents (63.3%) expressed a high level of interest in cervical cancer prevention. The results of the study showed that the majority of respondents were aged 26–35 years (41.8%) and had a high school education (45.9%). The behavior of the respondents fell into the “good” category for 56 individuals (57.1%), while 62 respondents (63.3%) expressed a high level of interest in cervical cancer prevention. The results of the Chi-Square test analysis indicate a significant association between the health behaviors of women of reproductive age and their interest in cervical cancer prevention (p = 0.001). The educational activities provided also improved participants’ knowledge, attitudes, and motivation to undergo early detection through IVA screening and Pap smears. It is concluded that good health behaviors play a crucial role in increasing the interest of women of reproductive age in cervical cancer prevention. Therefore, ongoing health education must continue to be implemented to increase screening coverage and reduce the incidence of cervical cancer.